Answer:
[tex]16i\sqrt{2}[/tex]
Step-by-step explanation:
Given expression:
[tex]2\sqrt{-50}+\sqrt{-72}[/tex]
Rewrite -50 as (25 · -2) and -72 as (36 · -2)
[tex]\implies 2\sqrt{25\cdot -2}+\sqrt{36 \cdot -2}[/tex]
[tex]\textsf{Apply radical rule} \quad \sqrt{ab}=\sqrt{a}\sqrt{b}:[/tex]
[tex]\implies 2\sqrt{25}\sqrt{-2}+\sqrt{36}\sqrt{-2}[/tex]
Rewrite 25 as 5² and 36 as 6²:
[tex]\implies 2\sqrt{5^2}\sqrt{-2}+\sqrt{6^2}\sqrt{-2}[/tex]
[tex]\textsf{Apply radical rule} \quad \sqrt{a^2}=a, \quad a \geq 0[/tex]
[tex]\implies 2 \cdot 5\sqrt{-2}+6\sqrt{-2}[/tex]
Simplify:
[tex]\implies 10\sqrt{-2}+6\sqrt{-2}[/tex]
[tex]\implies 16\sqrt{-2}[/tex]
[tex]\textsf{Apply radical rule} \quad \sqrt{-a}=\sqrt{-1}\sqrt{a}:[/tex]
[tex]\implies 16\sqrt{-1}\sqrt{2}[/tex]
[tex]\textsf{Apply imaginary number rule}\quad \sqrt{-1}=i[/tex]
[tex]\implies 16i\sqrt{2}[/tex]
Learn more about radical rules here:
https://brainly.com/question/28106222